2020
DOI: 10.1016/j.heliyon.2020.e04949
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory technology “RegTech” and money laundering prevention in Islamic and conventional banking industry

Abstract: This study aims to illustrate the impact of adopting Regulatory technology (RegTech) innovations in banks on money laundering prevention effectiveness using Bahrain as a case study. Bahrain has strived to position itself as the banking center of the Arabian Gulf, hence the results of this novel research are informative of the practices in the region. The primary data for this study was collected through a survey instrument distributed to 100 bankers working in Bahrain with expertise in compliance. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 10 publications
3
48
0
Order By: Relevance
“…Customers' desire for AIB services may be influenced by their awareness of services (Turki et al, 2020;Balushi et al, 2018;Lassoued et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Customers' desire for AIB services may be influenced by their awareness of services (Turki et al, 2020;Balushi et al, 2018;Lassoued et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Customer values, as well as the service's compliance with religious and societal values, might affect the decision to utilize Islamic banking services. (Turki et al, 2020). Previous research has indicated that customer AIB services are positively linked with compatibility (Ashraf et al, 2016;Lassoued et al, 2018).…”
Section: Perceived Compatibility (Pc)mentioning
confidence: 98%
See 3 more Smart Citations